Capital financeiro e commodities: um estudo das bolsas de valores de Mumbai, São Paulo e Joanesburgo - Margarida Maria C. L. Mattos (Confins)
Along the history, the role played by the cities was important both for the development of the mercantile capitalism as for the growth of the industrial capitalism, by means of the national markets building. The financial capital, whose logic is inherent in a globalized environment, was also constituted at the cities, reinforcing the relationships among markets, including the emergent ones. In these countries some of the cities are highlighted and got strategic importance incorporating functions that transcend the boundaries of the countries where they are located. In this article are taken three of the cities of these countries – Mumbai, São Paulo and Johannesburg – and examined the composition of their Stock Exchange indices. These organizations, due to its multiscale dimensions, lead to the comprehension of the logic, the direction and the intensity of the investments insertion in the global economy. The study shows not only the weight of commodities in correlation with those indexes, but also the regionalized distribution of the investments referred to each of the Stock Exchanges.